PKM Kelompok Anggota Karang Taruna RW 07 Tentang Pengenalan Media Informasi Blog Dengan Platform Google Site - Syamsiah Syamsiah; Agus Darmawan; Nunu Kustian; Vici Febriana (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
his Abdimas aims to explain the initiative of the Karang Taruna RW 07 Member Group in introducing information media in the form of blogs using the Google Site platform. The main objective of this project is to improve access to information and communication between member groups, as well as facilitate the exchange of information with the surrounding community. This service includes practical steps in creating and managing a website with Google Site, as well as its impact on increasing member involvement and understanding of information technology among the group. Through collaboration and internal training, the Karang Taruna RW 07 Member Group hopes to create a more effective forum for sharing information and promoting social activities in their environment. This research provides insight into the application of information technology in village-level community organizations and its impact on the quality of communication and member engagement.